Where things come back : a novel - Whaley, John Corey (New York : Atheneum Books for Young Readers, 2011)
Seventeen-year-old Cullen's summer in Lily, Arkansas, is marked by his cousin's death by overdose, an alleged spotting of a woodpecker thought to be extinct, failed romances, and his younger brother's sudden disappearance.
Ages 14 up.
Keywords: Missing persons -- Fiction; Interpersonal relations -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Extinct animals -- Fiction; Family life -- Arkansas -- Fiction; Arkansas -- Fiction; Missing persons -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Extinct birds -- Juvenile fiction; Families -- Arkansas -- Juvenile fiction; Printz Medal; Arkansas -- Juvenile fiction